A novel thromboxane receptor antagonist, nstpbp5185, inhibits platelet aggregation and thrombus formation in animal models - Huang, Shiu-Wen; Kuo, Heng-Lan; Hsu, Ming-Tsung; Tseng, Yufeng Jane; Lin, Shu-Wha; Kuo, Sheng-Chu; Peng, Hui-Chin; Lien, Jin-Cherng; Huang, Tur-Fu (Thrombosis and Haemostasis, 2016)
A novel benzimidazole derivative, nstpbp5185, was discovered through in vitro and in vivo evaluations for antiplatelet activity. Thro-maboxane receptor (TP) is important in vascular physiology, haemostasis and pathophysiological thrombosis. Nstpbp5185 concentration-dependently inhibited human platelet aggregation caused by collagen, arachidonic acid and U46619. Nstpbp5185 caused a right-shift of the concentration-response curve of U46619 and competitively inhibited the binding of 3H-SQ-29548 to TP receptor expressed on HEK-293 cells, with an IC50 of 0.1 μM, indicating that nstpbp5185 is a TP antagonist. In murine thrombosis models, nstpbp5185 significantly prolonged the latent period in triggering platelet plug formation in mesenteric and FeCl3-induced thrombi formation, and increased the survival rate in pulmonary embolism model with less bleeding than aspirin. This study suggests nstpbp5185, an orally selective antithrombotic agent, acting through blockade of TXA2 receptor, may be efficacious for prevention or treatment of pathologic thrombosis.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Benzimidazole; mouse thrombotic model; thromboxane receptor antagonist